Simulation training significantly improves the performance of novice students achieving the standard transesophageal echocardiography views - Aleksander Siniarski; Paweł Piątek; Aleksandra Karcińska; Alicia del Carmen Yika; Kamil Szostek; Tomasz Dziwiński; Maciej Stąpór; Karolina Golińska-Grzybała; Adam Piórkowski; Andrzej Gackowski (BMC Medical Education)
Abstract Background Transesophageal echocardiography (TEE) is an important cardiovascular imaging modality, offering detailed images surpassing other techniques, including transthoracic echocardiography. TEE's efficacy relies on skilled physicians operating the probe. Adequate TEE training is often overlooked, leading to potential patient discomfort or harm during TEE examinations. TEE simulators address this gap, providing a safe environment for practitioners to enhance their skills. Aims Our study aims to assess the progress of TEE novices, namely medical students following a specific learning protocol with a TEE simulator, hypothesizing significant improvements in the time and movements required for simulated TEE views after training. Methods The study protocol encompassed the selection of predetermined simulated TEE projections (n = 16), in accordance with the American Society of Echocardiography guidelines, to facilitate a comprehensive examination involving essential TEE manipulations. Students were provided with unrestricted access to video lectures and subsequently underwent the initial assessment (Test 1). Following this, they had a period of one to four weeks for training on the simulator, with unlimited access to TEE simulation. Test 2 was then administered, and calculations were conducted based on the discrepancies between both tests. Analytical parameters comprised the precision of the TEE view, examination time, and the randomity of probe movement (RAR index). Subsequently, two independent experts rigorously compared the two tests and graded each student's performance change as improvement, no change or worsening. Results Twenty-six Jagiellonian University Medical College students (median age: 22.5, IQR: 22–24) in the 2nd to 6th year and 50% females, with no prior experience of echocardiography or TEE simulator use participated in the study. Students familiarized themselves with online lectures before executing an identical TEE examination protocol. Median duration between Test 1 and Test 2 was 18 days (IQR: 12–28). First, after TEE simulated training, students exhibited a higher frequency of successfully completing the TEE examination without major errors (grade: passed) (P = 0.039). Additionally, precision significantly increased at Test 2 (P < 0.001). The total duration of the simulated TEE examination was significantly shorter in Test 2 than in the initial test (P < 0.001). Furthermore, the RAR index for ante/retroflexion was substantially lower in Test 2, while probe rotation remained similar between tests. Overall, student progress was evident in the majority of cases, with only 2 students showing no improvement after 1–4 weeks of voluntary self-training with the TEE simulator, and 2 more demonstrating a neutral outcome. Conclusions The use of a TEE simulator is valuable for learning how to perform proper and safe simulated TEE examinations. It is effective even for students without prior echocardiographic experience, improving precision, shortening examination time, and reducing unnecessary movements during simulated TEE. TEE simulation is an ideal learning tool for both students and cardiovascular clinicians to minimize mistakes in their practice.